Mudanças em diretrizes de Basiléia e o impacto na alocação de capital de risco operacional em instituições financeiras brasileiras - Caldas, Marcelo Petroni (2018)
This thesis approaches capital availability of Brazilian banks to face operational risks due to business or new financial crisis as saw it recently in subprime credit crunch that caused the collapsed of many banks worldwide due to flaws in risk management. This research aimed to study whether there is a relationship between regulatory changes and capital allocation for operational risk at the nine biggest financial institutions in the Brazilian market, as released by Brazilian Central Bank, and the impact in banks capital balance and lastly in the Brazilian economy considering credit availability for banking customers. The theory used is based on the literature that focuses on cross border banking rules and the regulatory push concept, organizational ecology and the pecking order theory of capital structure. The methodology adopted is phenomenology with qualitative data analysis. Preliminary conclusions show if the rule is changed, capital allocation is impacted and shareholders have to invest more money.